Eugene Onegin and Russian Identity - Murillo, Luis (The Toro Historical Review, 2024)
This paper examines the Russian novel Eugene Onegin and the extent to which different themes of the book are reflective of a Russian identity crisis. Analyzing the book from a historical perspective, this essay shows how the author Alexander Pushkin cleverly drafted a novel demonstrative of this identity crisis and the influence of foreign works in Russia.